Ultrastructural and morphological effects in T-Lymphoblastic leukaemia, CEM-SS Cells following treatment with Nordamnacanthal and Damnacanthal from Roots of Morinda elliptica - Saiful Yazan, Latifah; Gopalsamy, Banulata; Abdul Rahim, Raha; Ali, Abdul Manaf; Lajis, Nordin (MDPI, 2021)
Background: Morinda elliptica (family Rubiaceae), locally known as ‘mengkudu kecil’, has been used by the Malays for medicinal purposes. Anthraquinones isolated from the roots of Morinda elliptica, namely nordamnacanthal and damnacanthal, have been widely reported to exhibit anticancer and antioxidant properties in various cancer models in vitro and in vivo. Aim: This study analyzed the morphological and ultrastructural effects of damnacanthal and nordamnacanthal on T-lymphoblastic leukemia CEM-SS cells. Method: Light microscopy, Giemsa staining, Wright’s staining, scanning electron microscopy, and transmission electron microscopy were carried out to determine apoptosis, necrosis, and ultrastructural changes that occurred within the cells. Results: The outcomes showed that these compounds induced cell death by apoptosis and necrosis, specifically at higher doses of 10 and 30 μg/mL. Condensation and fragmentation of the nuclear chromatin, which further separated into small, membrane-bound vesicles known as apoptotic bodies, were observed in the nuclei and cytoplasm. The plasma membranes and cytoskeletons also showed marked morphological changes upon treatment with damnacanthal and nordamnacanthal, indicating apoptosis. Conclusion: Therefore, we report that damnacanthal and nordamnacanthal exhibit anticancer properties by inducing apoptosis and necrosis in CEM-SS cells, and they have potential as a drug for the treatment of T-lymphoblastic leukemia.